Spare Parts Marketing Development Strategy Using SWOT and BMC Approaches: A Case Study on PT. Persada Utama Diesel - Prasetyo Wicaksono; Eva Ervani (Riviera Publishing, 2024)
This study aims to develop a spare parts marketing strategy using SWOT and Business Model Canvas (BMC) approaches at PT Persada Utama Diesel. Globalization has encouraged economic growth in various sectors, including exports and imports. However, international business activities also have risks that must be managed properly. Effective risk management can increase investor confidence, maintain company reputation, and ensure long-term business sustainability. This research uses a qualitative approach with a case study on PT Persada Utama Diesel. Data were collected through interviews, observations, and documentation studies. SWOT analysis and Business Model Canvas (BMC) were used to develop a spare parts marketing strategy. The results of the SWOT analysis identify the strengths, weaknesses, opportunities, and threats facing the company. Based on the BMC analysis, the company's current business model was also evaluated and developed. The recommended spare parts marketing strategy includes improving operational efficiency, developing a global distribution network, and strengthening strategic partnerships. The application of SWOT and BMC approaches is effective in developing a spare parts marketing strategy that can help PT Persada Utama Diesel in facing challenges and capitalizing on opportunities in an increasingly competitive international market.